Implementation of Additive Ratio Assessment Method in Decision Making on Fertilizer Supplier Selection at BBTPH Banyumas - Dasril Aldo; Yohani Setiya Rafika Nur; Annisaa Utami (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
The purpose of this study is to solve problems in the selection of fertilizer suppliers at BBTPH Banyumas by proposing a decision support system (DSS). The quality of fertilizer supplier performance that is less than meeting standards can have a direct effect on crop yields, affect the level of efficiency, and decrease the quality of horticultural commodities. Therefore, this study aims to obtain decisions on the most feasible suppliers to be partners in supplying fertilizers. The method used in this study is the Additive Ratio Assessment (ARAS) method which is a method for alternative ranking based on specified criteria. The criteria used are in the form of criteria data, namely quality, price, service, delivery, product, and warranty. Fertilizer supplier data is obtained from BBTPH Banyumas and processed using the ARAS method. The stages carried out are identifying criteria, weighting, determining alternatives, evaluating alternatives, calculating the score of each alternative and choosing the suggested solution. The results showed that the best fertilizer supplier was supplier A with an ARAS value of 0.421. Supplier A has advantages in price, quality, and reputation criteria. This research can provide recommendations to BBTPH Banyumas in choosing fertilizer suppliers that suit their needs and preferences. The ARAS method is very useful in solving complex problems and involves many factors. By using this approach, the decisions taken become more objective and supported by clear data. Therefore, the ARAS method can be adopted by other organizations to address similar problems.